PEMANFAATAN CITRA SATELIT LANDSAT 8 UNTUK MEMETAKAN HUTAN MANGROVE WISATA BAHARI PANTAI KARANGANTU, TELUK BANTEN - Kiran Aulia Putri; Willdan Aprizal Arifin; La Ode Alam Minsaris (Universitas Muhammadiyah Gorontalo, 2022)
Mangrove marine tourism is one of the tourism sectors involved in large and important projects in tourism development. The transformation of PPN Karangantu from a protected area to marine tourism has caused environmental damage. This continued focus on mass tourism has resulted in environmental damage and pollution of the mangrove area found in PPN Karangantu. The aim of the study was to calculate the area of mangrove forest, the accuracy value of mangrove density and changes in conditions due to the existence of the Karangantu Beach marine tourism area in the last 5 years. The research method uses a mixed method to identify mangrove areas by visually analyzing landsat 8 spectral values using the Google Earth Engine (GEE) platform and by image processing for 2018-2022. The results showed that in 2018 the area of mangrove land was 17.04 ha, which decreased drastically in 2019 to 6.28 ha due to an oil spill that was carried away from Karawang Waters. In 2020 it will be 10.6 ha, in 2021 it will be 9.56 ha and in 2022 it will be 7.32 ha. This decrease area is due to marine tourism activities which damage the mangrove ecosystem land and many visitors do not protect the ecosystem. The use of GEE can provide an overview of the capabilities of Landsat 8 satellite imagery in mapping the mangrove forests in Karangantu Beach.